Gestures and Their Meanings of Main Character in Daniel’s Movie Everything Everywhere All at Once (2022) - Fauziah Khairani Lubis; Syamsul Bahri (Randwick International of Social Science Journal, 2023)
Gesture is a unique nonverbal communication signal, whereby a person conveys a message or expresses himself through conscious or unconscious movements, body movements, and facial expressions" (Vijay, 2013). This study aims to analyze gestures and meaning based on the context of gestures supported by utterances. According to Sugiyono (2013: 13), this research employs a descriptive qualitative methodology. This study uses the theory of McNeil (2005) that classifies gestures into four types, namely Iconic, Deictic, Metaphor, and Beat. The data used in this research is in the form of screenshots taken from the movie "Everything Everywhere All at Once (20"2)" by Daniel. Four types of gestures are found in the movie, as the researcher has done in the analysis. There are 122 data found. There are 11 (9%) data as iconic gestures, 22 (18%) data as deictic gestures, 15 (12%) data as metaphor gestures, and 75 (61%) data as beat gestures. From the data analyzed, the meaning of the gesture is supported by the utterances in dialog (Semantic Meaning). Some gestures meaning is unclear if they are not accompanied or supported by semantic meaning or utterances. Meanwhile, some data do not have a cultural meaning and no relation to the semantic meaning, such as beat type. A beat gesture is a rhythm of speech as a compliment.